Fermi blockade of the strong electron–phonon interaction in modelled optimally doped high temperature superconductors - Andrey S. Mishchenko (Nature Portfolio, 2021)
Abstract We study how manifestations of strong electron–phonon interaction depend on the carrier concentration by solving the two-dimensional Holstein model for the spin-polarized fermions using an approximation free bold-line diagrammatic Monte Carlo method. We show that the strong electron–phonon interaction, obviously present at very small Fermion concentration, is masked by the Fermi blockade effects and Migdal’s theorem to the extent that it manifests itself as moderate one at large carriers densities. Suppression of strong electron–phonon interaction fingerprints is in agreement with experimental observations in doped high temperature superconductors.